Grammoplites vittatus (Valenciennes), (Scorpaeniformes, Platycephalidae), removed from synonymy with Grammoplites scaber (Linnaeus) - Knapp, Leslie W.; Imamura, Hisashi (Zootaxa, 2014)
Grammoplites vittatus (Valenciennes), often previously overlooked by authors or regarded as a junior synonym of G. scaber (Linnaeus), is shown here to be a valid species.  It has more gill rakers (7–8) then G. scaber and G. knappi (usually 6) and a narrower interorbital width than G. scaber.  A key to the species of Grammoplites Fowler is  given.